2018
DOI: 10.31768/2312-8852.2018.40(4):261-267
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF THE GENETIC ABNORMALITIES, EPIGENETIC AND microRNA IN THE PROGNOSIS OF CHRONIC LYMPHOCYTIC LEUKEMIA

Abstract: Chronic lymphocytic leukemia (CLL) is increased proliferation of B-cells with peripheral blood and bone marrow involvement, which is usually observed in older people. Genetic mutations, epigenetic changes and miRs play a role in CLL pathogenesis. Del 11q, del l17q, del 6q, trisomy 12, p53 and IgVH mutations are the most important genetic changes in CLL. Deletion of miR-15a and miR-16a can increase bcl2 gene expression, miR-29 and miR-181 deletions decrease the expression of TCL1, and miR-146a deletion prevents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…FISH study demonstrated deletion of 11q and interstitial deletion of 13q (67-73% of cells). Deletions of [5]. Furthermore, deletions of 13q, again seen in this case, are demonstrated in approximately 68% of CLL cases [5].…”
Section: Case Presentationsupporting
confidence: 67%
See 1 more Smart Citation
“…FISH study demonstrated deletion of 11q and interstitial deletion of 13q (67-73% of cells). Deletions of [5]. Furthermore, deletions of 13q, again seen in this case, are demonstrated in approximately 68% of CLL cases [5].…”
Section: Case Presentationsupporting
confidence: 67%
“…Deletions of [5]. Furthermore, deletions of 13q, again seen in this case, are demonstrated in approximately 68% of CLL cases [5]. Deletions are a poor prognostic marker thus suggesting evolution of the cell line in this patient.…”
Section: Case Presentationsupporting
confidence: 61%
“…42 As previously stated, the clinical stage of the disease, the mutational status of the IGHV locus, and absence or mutation of the TP53 gene are considered as the most valid prognostic markers in this hematological malignancy 6,7,15,26 ; other prognostic factors are also taken into consideration. 43 In the current study, mutations of TP53, SF3B1, and NOTCH1 and cytogenetic markers were not examined.…”
Section: Discussionmentioning
confidence: 91%
“…Del13q, specifically involving band 13q14 on which miR-15a and miR-16a are located, seems to be the most frequently observed cytogenetic aberration in CLL and associated with a good prognosis [ 54 , 55 ]. Patients with isolated del13q need treatment sooner and have a shorter OS if the cells with del13q ≥ 60% [ 56 ].…”
Section: Introductionmentioning
confidence: 99%